2022
DOI: 10.3390/s23010172
|View full text |Cite
|
Sign up to set email alerts
|

Interference Analysis of 5G NR Base Stations to Fixed Satellite Service Bent-Pipe Transponders in the 6425–7125 MHz Frequency Band

Abstract: Future deployment of 5G NR base stations in the 6425–7125 MHz band raises numerous concerns over the long-term impact on the satellite transponders located in geostationary orbit. To study this impact and understand whether 5G NR may cause adverse effect to the spaceborne receivers, the research which estimated the interference levels to the satellite bent pipe links was done. The study presents the evaluation of aggregate interference from 5G NR base stations located inside the victim satellites’ footprints u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…After C/N and C/(N + I) were calculated, it is possible to calculate the Eb/No. The Eb/No is directly related to the C/N value, and can be expressed as follows [ 19 ]: where E b / N 0 represents the ratio of energy per bit to spectral power density (dB); N is the noise level in a reference bandwidth (dBW); I represents the interference level in a reference bandwidth (dBW); R is the data rate (kbit/s); B is the reference bandwidth (kHz); and C is the carrier bandwidth [ 20 ].…”
Section: Methodology Of Simulationsmentioning
confidence: 99%
“…After C/N and C/(N + I) were calculated, it is possible to calculate the Eb/No. The Eb/No is directly related to the C/N value, and can be expressed as follows [ 19 ]: where E b / N 0 represents the ratio of energy per bit to spectral power density (dB); N is the noise level in a reference bandwidth (dBW); I represents the interference level in a reference bandwidth (dBW); R is the data rate (kbit/s); B is the reference bandwidth (kHz); and C is the carrier bandwidth [ 20 ].…”
Section: Methodology Of Simulationsmentioning
confidence: 99%
“…Pastukh et al [22] provided a comprehensive review of the state-of-the-art literature on the impact and implementation of the aforementioned technologies into AV architectures, along with the challenges faced by each of them. Biswas and Wang [23] proposed a novel framework named Pyramid that unleashes the potential of edge artificial intelligence (AI) by facilitating homogeneous and heterogeneous hierarchical machine learning (ML) inferences.…”
Section: Related Workmentioning
confidence: 99%
“…The articles in [25,26] focus on the coexistence of 5G networks with other services in the 6425-7125 MHz band. They employ Monte Carlo simulation to address interference issues.…”
Section: Introductionmentioning
confidence: 99%
“…Different protection criteria, like I/N and C/I, were used to determine suitable separation distances, especially in co-location scenarios within a single administration. In [26], the research evaluated aggregate interference from 5G base stations within satellite footprints, considering factors like signal-to-noise degradation and bit error rates for fixed-satellite service (FSS) bent-pipe transponders. The results suggested that coexistence between 5G NR and satellite systems in this frequency range is feasible, with no significant adverse effects on satellite link performance.…”
Section: Introductionmentioning
confidence: 99%